Promises I can keep: why poor women put motherhood before marriage - Edin, Kathryn; Kefalas, Maria (University of California Press, 2011)
Millie Acevedo bore her first child before the age of 16 and dropped out of high school to care for her newborn. Now 27, she is the unmarried mother of three and is raising her kids in one of Philadelphia's poorest neighborhoods. Would she and her children be better off if she had waited to have them and had married their father first? Why do so many poor American youth like Millie continue to have children before they can afford to take care of them? Over a span of five years, sociologists Kathryn Edin and Maria Kefalas talked in-depth with 162 low-income single moms like Millie to learn how they think about marriage and family. Promises I Can Keep offers an intimate look at what marriage and motherhood mean to these women and provides the most extensive on-the-ground study to date of why they put children before marriage despite the daunting challenges they know lie ahead.